Knowledge, attitude and perception of private practitioners based in Gauteng, South Africa, regarding evidence-based practice - De Wet, Wouter (Stellenbosch : University of Stellenbosch, 2015)
Background Evidence-based medicine (EBM) involves the care of patients using the best available evidence from the results of good quality clinical research to guide clinical decision making 1 – 3. By incorporating the principles of Evidence-based Medicine (EBM), the family practitioner would be able to treat a patient according to the best clinical research available. This principle is implemented widely in the USA, Canada, the United Kingdom and Europe. In South Africa, however, EBM is not yet as widely incorporated into family practice. This is so despite the plethora of websites available to practitioners and the relative ease with which applicable research evidence can be found. Very few published studies are available regarding EBM or Evidence–based Practice (EBP) in the South African context. The findings of this study would thus highlight reasons and/ or barriers preventing family practitioners from implementing EBM in their respective practices. This could also lead to further research into possible methods of implementation of EBM into South African family practices. Aim: The aim of the study was to describe the perceptions, knowledge and attitudes of private practitioners regarding evidence based practice and to identify the barriers encountered in evidence based practice. Methods A questionnaire survey of general practitioners in Gauteng, South Africa, was conducted. Questionnaires were distributed to a random sample of practitioners in the Gauteng region. Two hundred and twenty one (221) practitioners participated in the survey and responded to questionnaires mailed to them. The questionnaire was mailed, faxed or e-mailed to the practitioners, which they then completed and returned for statistical analysis. Study design The study design is that of quantitative, statistical analysis (descriptive cross-sectional survey). Setting General practitioners were randomly selected from a list of practitioners in the Gauteng Province. Doing a nationwide survey would have been a mammoth undertaking. It was therefore decided to limit the research to one province and therefore it was only concentrated on practitioners practicing in the Gauteng area. Results It is interesting to note that of the two hundred and twenty one participants in this study; only 10% of the practitioners were against using EBM in their practices. This, however, stands in stark contrast to the 56% of practitioners who do not implement EBM in their practices or make use of the EBM principle at all. The major barriers preventing practitioners from implementing EBM is depicted in the following graph: Lack of time and the training in aspects of Evidence-based medicine were the main barriers preventing the full scale implementation of EBM in family practices in Gauteng.